Perception of health students about Integrative Practices in Primary Healthcare Units (Research, Society and Development, 2025)
This study aimed to analyze the knowledge and interest of health students regarding Integrative and Complementary Practices (PICS) in the context of Primary Healthcare. It is an exploratory-descriptive, cross-sectional, and quantitative study conducted with 689 students from various courses at the Universidade Municipal de São Caetano do Sul between 2021 and 2022. Data were collected through a structured questionnaire applied electronically. Results indicated that 41% of students reported knowledge about PICS, while 58% were unaware of these practices. However, 89% expressed interest in learning more about the topic during their studies. Among respondents, 48% reported that practical activities in Primary Healthcare Units (UBS) included contact with PICS, with Acupuncture and Phytotherapy being the most frequently identified practices. The study concludes that there is a significant gap in knowledge about PICS among health students, despite the high interest demonstrated. Including PICS-related content in academic curricula and expanding practical experiences can contribute to the training of professionals better prepared to meet the demands of Primary Healthcare within the SUS.